2023
DOI: 10.1002/lsm.23677
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring lesion activity on primary teeth with CP‐OCT and SWIR reflectance imaging

Abstract: Objective: The purpose of this study was to use cross polarization optical coherence tomography (CP-OCT) and short wavelength infrared imaging (SWIR) reflectance imaging to monitor changes in the structure and activity of early occlusal caries on primary teeth over a period of 6 months during intervention with fluoride. Methods: Participants (n = 29) aged 6−10 each with two suspected active occlusal lesions on primary teeth completed the study. Fluoride varnish was applied to tooth surfaces every 3-months and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Based on this study and recent studies [25, 26], it appears that %Δ I is not a reliable parameter to discriminate between active and arrested lesions and is not suitable for in vivo measurements since the depth and severity of the lesions is not known ahead of time. The other three parameters that reflect the kinetics of the dehydration process; delay, % I fin , and rate are less dependent on the lesion depth and severity and are better suited for clinical use.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…Based on this study and recent studies [25, 26], it appears that %Δ I is not a reliable parameter to discriminate between active and arrested lesions and is not suitable for in vivo measurements since the depth and severity of the lesions is not known ahead of time. The other three parameters that reflect the kinetics of the dehydration process; delay, % I fin , and rate are less dependent on the lesion depth and severity and are better suited for clinical use.…”
Section: Discussionmentioning
confidence: 80%
“…Such surfaces are more challenging for lesion activity assessment using time‐resolved SWIR reflectance imaging due to the highly convoluted topography. In the first clinical study to assess lesion activity in vivo using time‐resolved SWIR reflectance imaging, lesions located on the occlusal surfaces of primary teeth were chosen to ensure that most of the lesions would be active [26]. The study showed the potential of using the delay to discriminate between active and arrested lesions however there was considerable difficulty in sufficiently dehydrating lesions in these areas in 30 s. In addition, many of the acquired curves were noisy or incomplete preventing the calculation of kinetic information from the curves such as rates or % I fin [26].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations